Education On Making Luti Gendang And Innovation Of Luti Gendang Products At State Elementary School 011 Sekupang Batam - Agung Arif Gunawan; Rosie Oktavia Puspita Rini; Hari Sandi Atmaja; Caroline Jeklin Seda; Chily Robillah (JURNAL KEKER WISATA, 2026)
This Community Service (PKM) activity aims to provide education on making luti gendang and innovation of luti gendang products to students of SD Negeri 011 Sekupang Batam. Luti gendang is a traditional food typical of the Riau Islands that has cultural value and economic potential. The activity was carried out through counseling methods, demonstrations, direct practice, and interactive discussions to 80 students in grades 4 and 5. The material provided included an introduction to traditional culinary, food safety, sanitation and hygiene, and culinary product innovation. The results of the activity showed an increase in students' knowledge about traditional culinary and the importance of healthy and safe food. In addition, students showed high enthusiasm in the practice of making luti gendang and product innovation. This activity is expected to increase awareness of the younger generation towards the preservation of local culinary culture and encourage creativity and healthy food consumption patterns from an early age